2020
DOI: 10.1111/1471-0528.16323
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylated fibronectin point‐of‐care test for diagnosis of pre‐eclampsia in a low‐resource setting: a prospective Southeast Asian population study

Abstract: Objective To determine the performance of a glycosylated fibronectin (GlyFn) point‐of‐care (POC) test for pre‐eclampsia (PE) in a large Southeast Asian cohort (India) in comparison to previously described biomarkers. Design A total of 798 pregnant women at ≥20 weeks of gestation were enrolled in a prospective case‐control study. Study participants included 469 normotensive women with urinary mg protein/mmol creatinine ratio <0.3, 135 with PE (hypertension with urinary mg protein/mmol creatinine ratio ≥0.3) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 45 publications
2
15
1
Order By: Relevance
“…17 Overall biomarker performance was not different between early-versus late onset PE, or between non-severe and severe PE. 25 A significant proportion of subjects clinically stratified as GH were positive for PE biomarkers and also exhibited a higher frequency of preterm birth than control patients. 25…”
Section: Perinatal Outcomementioning
confidence: 95%
See 1 more Smart Citation
“…17 Overall biomarker performance was not different between early-versus late onset PE, or between non-severe and severe PE. 25 A significant proportion of subjects clinically stratified as GH were positive for PE biomarkers and also exhibited a higher frequency of preterm birth than control patients. 25…”
Section: Perinatal Outcomementioning
confidence: 95%
“…24 The LumellaTM GlyFn POC test, (GlyFn point-of-care test for diagnosis of PE) has been validated in a low/middle-income country setting for PE diagnosis. 25 It has been concluded in the study that this may be a useful diagnostic tool for early identification, and appropriate early institution of treatment, so as to reduce adverse maternal and fetal outcomes. 25 Alternative forms of fibronectin have been demonstrated to play a role in acute inflammation and ischemia, vascular remodeling and placental insufficiency and oxygen levels may contribute to altered glycosylation of glycoproteins like fibronectin.…”
Section: Introductionmentioning
confidence: 99%
“…PE pregnancies compared with non-PE pregnancies is consistent with that of a longitudinal and cross-sectional combined cohort study in Finnish women (n = 107), which reported significantly higher GlyFn in PE vs non-PE pregnancies in the first as well as later trimesters 11 . More recently, elevated GlyFn at ≥ 20 weeks' gestation was shown to be a short-term predictor for development of PE in Swiss and Indian cohort studies 12,13 . The association between serum levels of fibronectin and PE was reported as early as the 1980s 25 .…”
Section: Main Findingsmentioning
confidence: 99%
“…One potential alternative biomarker for PE is the glycosylated form of fibronectin (GlyFn). Raised GlyFn level was reported in pregnant women of differing ethnic backgrounds who developed PE after 20 weeks' gestation 11–13 . In addition, GlyFn was found to be elevated between 6 and 14 weeks' gestation in pregnancies that subsequently developed PE compared with those that did not 11 .…”
Section: Introductionmentioning
confidence: 96%
“…According to ACOG, preeclampsia has an incidence of about 2-8%, 5-7% are nulliparous and 2% of patients will develop eclampsia. (3,4) Preeclampsia along with the other subcategories of this hypersensitive disease spectrum are responsible annually for approximately 400,000 maternal deaths and six million perinatal fetal deaths while being considered risk factors for premature birth and underweight newborns.…”
mentioning
confidence: 99%